Efektivitas Pemilihan Kepala Daerah Melalui DPRD dan Pemilihan Secara Langsung Oleh Rakyat Dalam Sistem Demokrasi Indonesia - Muklis Muklis (SOSEK : Jurnal Sosial dan Ekonomi, 2021)
The journey of post-conflict local elections from the independence era to the reform era as it is now often changes the election mechanism. Starting from the direct election mechanism by the people to the indirect election mechanism chosen by the DPRD. Until its peak when Law No. 22 of 2014. The purpose of this study was to determine the effectiveness of indirect regional head elections through elections by the DPRD, the effectiveness of direct regional head elections through elections by the people, as well as obstacles to regional head elections through DPRD and local elections. directly by the people in a democratic system. The type of research used is empirical juridical research by conducting interviews, and in this case the data is processed using qualitative analysis. Based on the results of the study, the effectiveness of regional head elections through DPRD is indeed more effective because it can reduce the political budget that must be issued by the views of regional head candidates, and also minimizes/prevents clashes or debates in the community carried out between supporters of regional head candidates. The effectiveness of regional head elections through the people will better know what the vision and mission of the candidate pairs and the elected regional heads will have closer ties to the community because the community itself determines the figure who will lead their own region. Constraints in the election of regional heads through the DPRD are basically constrained because they cannot guarantee that the choices from the DPRD are in accordance with community expectations, while the obstacles in direct regional head elections include being constrained by the large political budget, causing conflict in the community due to frictions between the support of the candidate pair. In these areas, the large political costs that candidate pairs have to incur in nominating themselves are considered to have resulted in the candidates for regional heads committing corruption when they were elected and the high number of abstentions in some areas